Review of Fundamental Processes and Applications of Atoms and Ions - Lin C.D (World Scientific, 1994)
This collection of papers presents a review of this field, discussing topics including: atomic processes in thermonuclear fusion plasmas; progress in atomic collisions with multiple charged ions; and atomic and molecular multiphoton processes in intense laser fields.